Effect of Blue Light Color on Zn (II) and Cu (II) Metal Biosorption Using Tetraselmis chuii Microalgae - Dewi, Tanti Utami Utami; Setiawan, Adhi; Dzulfikar, Muhammad Hanif; Putri, Desita Ramadona Syah; Gunawan, Karina Larasati; Prianto, Haekal Irfan Titan; Firnandi, Rahmad (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2024)
Direct release of inorganic compounds Cu (II) and Zn (II) into water bodies can disrupt ecosystems. Using microalgae biosorbent Tetraselmis chuii (T. chuii) is a promising approach for removing these metals from wastewater. This study investigated the effect of blue light on the absorption of Cu (II) and Zn (II) by analyzing the contact time and initial concentration. Statistical analysis (MANOVA) revealed differences in the biosorption process due to the contact time and Cu (II) concentration (P <0.05). The results showed that the most effective Cu (II) removal occurred with a 60-minute contact time at a concentration of 5 mg/L, achieving a 67.07% removal rate. Zn (II) removal was also efficient under blue light conditions with a 60-minute contact time at the same concentration, yielding a 56.23% removal rate. Additionally, this process led to a substantial reduction in microalgae T. chuii cell density, by 76% for Cu (II) and 89.2% for Zn(II). Characterization analyses using Fourier-transform infrared spectroscopy (FTIR) and scanning electron microscopy confirmed the presence of functional groups in T. chuii microalgae, which are crucial for the biosorption process. This study underscores the potential of microalgae as effective biosorbents for mitigating inorganic compound pollution in wastewater.